Time-motion analysis and physiological responses to taekwondo combat in juvenile and adult athletes: A systematic review. - Santos, J. F. da Silva; Dias Wilson, V.; Herrera-Valenzuela, T.; Sander Mansur Machado, F. (Strength and Conditioning Journal, 2020)
Taekwondo is a complex combat sport characterized by high-intensity short activity and low-intensity activity and/or pause. This systematic review focused on which type of physical capacities and the main physiological adjustments that are demanded during official taekwondo matches. The search was performed in electronic databases in which 38 articles were selected. Taekwondo matches' characteristics, time-motion analysis, physical and physiological responses during prematch and postmatch were described. After analysis, practical recommendations were suggested regarding physical training prescriptions oriented to performance optimization of taekwondo athletes.